Neurological disorders associated with DNA strand-break processing enzymes. (January 2017) - Jiang, Bingcheng; Glover, J.N. Mark; Weinfeld, Michael
Highlights: Review of neurological diseases caused by mutated DNA strand-break repair enzymes. Brief description of the symptoms of the neurological disorders. Discussion of three proteins TDP1, APTX and PNKP involved and their mutation. Discussion of how their impairment may give rise to the neurological disorders. Abstract: The termini of DNA strand breaks induced by reactive oxygen species or by abortive DNA metabolic intermediates require processing to enable subsequent gap filling and ligation to proceed. The three proteins, tyrosyl DNA-phosphodiesterase 1 (TDP1), aprataxin (APTX) and polynucleotide kinase/phosphatase (PNKP) each act on a discrete set of modified strand-break termini. Recently, a series of neurodegenerative and neurodevelopmental disorders have been associated with mutations in the genes coding for these proteins. Mutations in TDP1 and APTX have been linked to Spinocerebellar ataxia with axonal neuropathy (SCAN1) and Ataxia-ocular motor apraxia 1 (AOA1), respectively, while mutations in PNKP are considered to be responsible for Microcephaly with seizures (MCSZ) and Ataxia-ocular motor apraxia 4 (AOA4). Here we present an overview of the mechanisms of these proteins and how their impairment may give rise to their respective disorders.